2010
DOI: 10.1577/m10-035.1
|View full text |Cite
|
Sign up to set email alerts
|

Length Reduction of Larval Yellow Perch and Freshwater Amphipods in RNAlater Solution

Abstract: Use of RNAlater (Ambion, Inc.) solution to preserve whole organisms for nucleic acid analysis is gaining popularity, in part because it effectively preserves both RNA and DNA without the need for freezing the organism. Similar preservatives have been shown to cause short‐term changes in animal length, and such changes must be accounted for as analyses progress. We examined the rates and degrees of shrinkage for freshwater amphipods Diporeia spp. and larval yellow perch Perca flavescens after preservation in RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…With larvae, as with eggs, we assumed shrinkage to be proportional (Foley et al. ). To evaluate maternal effects on larval survival and starvation resistance using only yolk‐sac energy reserves, we placed an additional randomly selected 20 larvae from each female into a 3.79 l tank filled with well water that was treated and sand‐column filtered to remove >90% of all particles larger than 5 μ m in diameter, and therefore contained no potential prey (R. Rode, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…With larvae, as with eggs, we assumed shrinkage to be proportional (Foley et al. ). To evaluate maternal effects on larval survival and starvation resistance using only yolk‐sac energy reserves, we placed an additional randomly selected 20 larvae from each female into a 3.79 l tank filled with well water that was treated and sand‐column filtered to remove >90% of all particles larger than 5 μ m in diameter, and therefore contained no potential prey (R. Rode, personal communication).…”
Section: Methodsmentioning
confidence: 99%
“…The copepods were counted and their viability checked before preserving them in RNAlater (Sigma). RNAlater can affect size (Foley et al, 2010), and the effect depends on the number of segments in the animal, i.e. the more segments, the larger effect.…”
Section: Measurements Of Egg Production Egg-hatching Success and Promentioning
confidence: 99%
“…RNAlater is a non-toxic supersaturated salt solution that would encourage strong leaching of water out of the organism. Other authors like Foley et al (2010) have observed that this medium damages calcified structures, such as otoliths, which are essential for studies on larval growth and ecology. However, this medium has important advantages for preserving organisms for nucleic acid analysis, partly because it effectively preserves both RNA and DNA without the need to freeze the organism (Gorokhova, 2005), making it especially useful in places where liquid nitrogen transport or freezing are not possible.…”
Section: Discussionmentioning
confidence: 96%